Factors affecting the profitability of insurance companies in Syria " Case Study" (Journal of Hama University, 2021)
The research aims to study the most important factors affecting the profitability of insurance companies represented by financial solvency, the size of risks in the insurance portfolio, the retention rate, the size of the company. The profitability of insurance companies measured by the rate of return on assets,This was studied in the National Insurance Company NIC and to study the impact between the variables we used a simple and then multiple regression analysis test, depending on the SPSS program, during the period from 2008 to 2019. It was found that there is a positive impact of financial solvency, as the solvency increases with the increase in the net written premiums, which in turn leads to an increase in profitability. The presence of a positive impact on the size of the risks, as an increase in the size of the risks leads to an increase in the absorptive capacity, which in turn leads to an increase in profitability. There is a strong positive impact of the retention rate on profitability, which helps the company to expand its investments. The existence of a negative impact of the size of the company on profitability, means that the more assets the company owns, the more that leads to its inability to exploit and employ its assets well in generating profits. It was found that all studied factors were able to explain 89.8% of the changes in the profitability of the National Insurance Company.